2017
DOI: 10.1159/000477780
|View full text |Cite
|
Sign up to set email alerts
|

Acalculous Cholecystitis: Is an Elective Interval Cholecystectomy Necessary

Abstract: Background: Acute acalculous cholecystitis (AAC) accounts for 5-10% of cases of acute cholecystitis. The advantage of interval cholecystectomy for patients with AAC is unclear. Therefore, a retrospective analysis of patients diagnosed with AAC at our institution was performed over a 5-year period. Methods: Patients were identified via hospital coding using the keywords “acalculous cholecystitis, cholecystostomy and gall bladder perforation.” Follow-up data was obtained by performing a retrospective review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…All patients had moderate-to-severe AC in our study, which further confirmed that PC is a technically safe choice. The recurrence rate after treatment with PC alone was 22.2% (6/27), which was significantly higher than the rates of 8.6% reported in the study of Abbas [ 8 ] and 2.7% reported in the study of Noh [ 7 ] but lower than the rate of 40% (2/5) reported in the study of Polistina [ 20 ]. Compared with the study of Noh, the high recurrence rate observed in our study may be related to the exclusion of Grade I AAC patients.…”
Section: Discussioncontrasting
confidence: 61%
“…All patients had moderate-to-severe AC in our study, which further confirmed that PC is a technically safe choice. The recurrence rate after treatment with PC alone was 22.2% (6/27), which was significantly higher than the rates of 8.6% reported in the study of Abbas [ 8 ] and 2.7% reported in the study of Noh [ 7 ] but lower than the rate of 40% (2/5) reported in the study of Polistina [ 20 ]. Compared with the study of Noh, the high recurrence rate observed in our study may be related to the exclusion of Grade I AAC patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Interestingly, only two patients had pre-existing asymptomatic cholecystolithiasis. Uncomplicated cases of postoperative cholecystitis could be managed with antibiotic treatment only [21]; in other cases laparoscopic cholecystectomy or open cholecystectomy were the treatments of choice, with percutaneous cholecystostomia as a definitive or bridge therapy in only two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this case, we would encourage consideration of prolonged antibiotics in cases of acalculous cholecystitis that could be secondary to c. canimorsus bacteremia. Given the risk of recurrence of this illness is very low, interval cholecystectomy is considered unnecessary in patients who recovery from acute acalculous cholecystitis [17].…”
Section: Discussionmentioning
confidence: 99%